Techniques and Assessment of Entrepreneurial Skill Training Module for Building Technology Graduates of Colleges of Education - Ibidapo, Abel Bamidele (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2021)
The study was carried out to investigate the techniques and assessment of entrepreneurial skill training module for building technology graduates of colleges of education. Three research questions were answered while three null hypotheses formulated were tested at 0.05 level of significance. The study adopted research and development design and was carried out in South-west Nigeria. The population for the study was 373 subjects. There was no sampling because of the manageable size of the population. The instrument for data collection was structured questionnaire. Five experts face- validated the instrument. The internal consistency of the questionnaire items was determined using Cronbach alpha reliability method and the reliability coefficients of 0.81 was obtained for instructional strategies required for the implementation of entrepreneurial skill training module, and 0.79 for evaluation techniques for assessing activities of graduates of building technology while 0.88 was obtained as the overall reliability coefficient value for the entire questionnaire items. Kuder Richardson 20 (KR20) was used to determine the internal consistency of the BTET and coefficient value of 0.78 was obtained. Out of 373 copies of structured questionnaire administered, only 223 copies were completed representing 59.78 percent return rate. Mean was used for answering the research questions while analysis of variance and covariance were employed for testing the null hypotheses. The findings of the study also revealed that the following number of instructional strategies and evaluation techniques were considered for implementing the entrepreneurial skill training module: instructional strategies 20 and evaluation techniques 15. The hypotheses tested revealed that there was a significant difference in the mean scores of building technology graduates trained with the developed modules and those taught without training module. The study also recommended that instructional strategies and evaluation techniques identified should be used for implementing the entrepreneurial skill training modules.